The state and islam in central asia: Administering the religious threat or engaging Muslim communities? - Alexander Wolters (PFH Private Hochschule Göttingen, 2014)
[Introduction ...] To analyze the transformation of the relations between secular states and the emerging Muslim societies in Central Asia this paper is divided into two sections. First I introduce into the cases by highlighting recent developments in religious awakening, "Islamic economics" and the "War on Terror". Second, I compare the state institutions, policies and actual practices to regulate the religious field in the five republics. I finally conclude on the politics of state engagement and the dynamics of state & society relations in Central Asia and possible further developments in Islamic economics in the region. I contend that development trajectories depend on the available space for political maneuvering that both state and society actors can use to engage one another. An open political system like the one in Kyrgyzstan promises more innovation and eventually more stable relations than a closed political system like the one in Uzbekistan, for example. Politics as an more or less open arena for exchange between opposing forces proves essential for the development of new institutions and practices, regardless of whether they are formalized or not. Only such social innovation allows states in the region to make use of Islam and religious faith in general to serve as a source for community strengthening and economic development, both much needed in the internationally pressured and politically instable region. To test my hypothesis I will rely for most parts on recent scholarly work about the "Islamic revival" in Central Asia and on research about the states' institutional settings. In addition news reports provide evidence on current events in the "War on Terror" and on "Islamic economic" practices in the region.
Keywords: 330